2018
DOI: 10.2106/jbjs.17.01518
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Tranexamic Acid Treatment and Risk of Cardiovascular Events or Death After Total Hip Arthroplasty

Abstract: Background: There have been concerns that the antifibrinolytic drug tranexamic acid (TXA) might increase the postoperative risk of cardiovascular events. Our objective was to determine whether perioperative TXA use is associated with cardiovascular events and death within 30 days after primary total hip arthroplasty (THA). Methods: We conducted a nationwide cohort study of cardiovascular outcomes after perioperative exposure to tranexamic acid during TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…IV TXA was not associated with an increased risk of VTE in patients with a history of VTE [22]. Further, a Danish registry study has demonstrated not only a reduced risk of arterial thrombosis (myocardial infarction and ischaemic stroke), but reduced rate of allcause mortality, if TXA is still administered in these patients [24].…”
Section: Discussionmentioning
confidence: 89%
“…IV TXA was not associated with an increased risk of VTE in patients with a history of VTE [22]. Further, a Danish registry study has demonstrated not only a reduced risk of arterial thrombosis (myocardial infarction and ischaemic stroke), but reduced rate of allcause mortality, if TXA is still administered in these patients [24].…”
Section: Discussionmentioning
confidence: 89%
“…At present, a large number of studies report that TXA is safe and effective in hip and knee joint replacement, regardless of the mode of administration, intravenous, topical, or combination [12][13][14][15]. However, no study has reported on the intravenous infusion of TXA in the acetabulum in terms of its effect on blood loss during the perioperative period in these fractures.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies report that TXA is safe and effective in hip and knee joint replacement, regardless of the mode of administration, intravenous, topical, or combination [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%